Chemical Regulation Effect of Water Use Efficiency of Maize Intercropping - Hongwei Chen; Ling Huang (Journal of Chemistry)
In order to solve the practical problems of large water demand and shortage of water resources in traditional wheat/maize intercropping, a planting method of changing stubble retention method is proposed in this paper. This method was used to study the effects of three stubble retention methods of traditional wheat straw incineration, straw return, and straw stubble on grain yield, water use efficiency (WUE), and economic benefits of wheat/maize intercropping. The results showed that, compared with the grain yield of burning and returning, the single cropping of wheat increased by 7.2% and 5.1%, the intercropping of wheat increased by 6.2% and 5.1%, the single cropping of corn increased by 4.7% and 2.5%, and the intercropping of corn increased by 7.2% and 3.3%, respectively; compared with the burned and returned WUE, wheat monoculture increased by 20.4% and 16.2%, respectively, wheat intercropping increased by 17.9% and 14.6%, respectively, corn monoculture increased by 16.7% and 10.9%, respectively, and corn intercropping increased by 11.8% and 17.0%, respectively. In terms of the average value of monoculture wheat, monoculture corn, and wheat/corn, the net benefits of incineration, turning, and stubble treatment are 10946, 11471, and 13454 yuan • hm−2, respectively. Considering the grain yield, water use efficiency, and net income, the standing stubble planting mode is the best planting mode of wheat/maize in this area.